Model Bisnis Strategi Umkm Surpet Collection Berbasis Business Model Canvas dan Analisis SWOT - Aulawi, Hilmi; Kurniawati, Rina; Ruari, Elgi Muhamad (Institut Teknologi Garut, 2025)
This study aims to determine the business model of Surpet Collection MSMEs using the SWOT Analysis and Business Model Canvas (BMC) methods. It also aims to identify the company's strategies through SWOT analysis and BMC that can be developed based on the BMC results, then design a business model to be implemented by Surpet Collection MSMEs as described in the BMC future approach, which is qualitative descriptive using SWOT analysis and business model canvas techniques. The three respondents who play an important role in Surpet Collection MSMEs in this study are improvements in the mapping of the current business model canvas, which has The results of the SWOT analysis provide an overview of the company's condition in quadrant III (WO). The strategy obtained from the SWOT matrix (WO).